The relationship between the coherent size, binding energy and dissociation dynamics of charge transfer excitons at organic interfaces. (19th October 2018) - Kafle, Tika R; Kattel, Bhupal; Wang, Ti; Chan, Wai-Lun
Abstract: At organic semiconductor interfaces, an electron and a hole can be bound Coulombically to form an interfacial charge transfer (CT) exciton. It is still under debate how a CT exciton can overcome its strong binding and dissociate into free carriers. Experimentally, capturing the evolution of the CT exciton on time (fs-ps) and length scales (nm) in which the dissociation process occurs is challenging. To overcome this challenge, time-resolved two photon photoemission spectroscopy is used to measure the binding energies and electronic coherent sizes of a series of CT states at organic interfaces, and capture the temporal dynamics of these CT excitons after their excitation. Using zinc phthalocyanine (ZnPc)/fullerene (C60 ) interface as a model system, it is shown that the interfacial CT process first populates a hot CT state with a coherent size of ~4 nm. Hot and delocalized CT excitons subsequently relax into CT excitons with lower energies and smaller coherent sizes. To correlate the CT exciton properties with the dissociation efficiency, we develop a method that exploits graphene field effect transistors to probe the rate and yield of free carrier generation at the interface. Our results show that exciton dissociation can be more efficient if one can extract electrons from the hot and delocalized CT state. We propose a cascade structure that would serve this purpose.